Efficiency of Plastic Fibres Waste on the Physico-Mechanical Properties of Mortars in Hot-Dry Conditions - Bendjillali, Khadra; Chemrouk, Mohamed (International Journal of Natural Sciences Research, 2016)
This experimental study was aimed at evaluating the effect of plastic fibres waste on the physical and mechanical performances of mortars prepared and conserved under hot-dry conditions. The used fibres are recycled polypropylene fibres coming from industrial waste. Two dosages of fibres are used 0.5 and 1 % by weight. The results showed that the exposition of mortars to hot-dry conditions reduces their long-term mechanical strength and increases their shrinkage. Under hot-dry conditions, the reinforcement of mortars by plastic fibres waste has a positive effect on their flexural and compressive strength. The shrinkage of mortars conserved under these conditions is reduced by the addition of plastic fibres waste.